From Vocabulary Building to Cultural Literacy: Implementing Contextual Teaching and Learning in Resource-Limited EFL Classrooms - Samsudin Samsudin; Sukarismanti Sukarismanti; La Ode Rasmin (Innovations in Language Education and Literature, 2025)
This study aims to explore the implementation of the Contextual Teaching and Learning (CTL) approach in teaching English in resource-constrained classrooms, with a focus on vocabulary development and cultural literacy. Using a multiple case study design with a qualitative approach, data was collected through semi-structured interviews with three lecturers at two educational institutions in West Nusa Tenggara, Indonesia. The findings show that the use of materials based on local wisdom, such as folklore and community history, significantly improves vocabulary acquisition, reading comprehension, and student motivation. In addition, CTL based on local contexts strengthens students' connections with teaching materials, enriches cultural literacy, and builds enthusiasm for learning. Despite resource limitations such as lack of access to technology and English language references, lecturers showed creativity in developing contextual teaching materials. This study contributes to filling the literature gap on local context-based language learning in a confined environment, as well as recommending the need for further research that expands population coverage and examines the long-term impact of the use of local materials in EFL teaching.